Imagination as Dynamism: Shaping Romantic Poetic Expressions - Sharma, Lok Raj (International Research Journal of MMC, 2023)
Imagination is one of the significant characteristics of Romantic poetry. Romantic poetry is subjective and clairvoyant. The subjectivity and extrasensory instinct are revived due to sharp imagination. The principal purpose of this article is to explicate imagination as dynamism in shaping Romantic poetic expressions. For this purpose, poetic works of Blake, Wordsworth, Coleridge, Shelley, Keats and Byron have been analyzed by considering imagination as the core of poems. This article employed a qualitative approach, drawing upon an extensive compilation of primary and secondary sources pertaining to Romantic poetry and the role of imagination in shaping literary expressions during the Romantic era. The primary sources consisted of poems by Romantic poets, while secondary sources encompassed scholarly articles, books, and critical essays, all of which contributed valuable insights into the topic and enhanced the comprehension of Romantic poetry and imagination. Materials for the study included terms, phrases, and assertions related to Romantic Imagination, and the method employed for analysis consisted of critical analysis. The primary focus of the analysis was to examine how Romantic poets explored and portrayed imagination across a wide range of their poetic works. This analytical process was executed subsequent to an extensive literature review on the subject matter. The study of this article will not only offer a comprehensive analysis of how imagination served as a dynamic force in shaping Romantic poetic expressions, but will also explore the broader implications of imagination in literature, culture, and art.